SUN’IY INTELLEKT TEXNOLOGIYALARI VA ULARNING INGLIZ TILINI MUSTAQIL O‘RGANISHDAGI AHAMIYATI - Komilova Sevinch (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the role and importance of artificial intelligence (AI) technologies in the modern education system, especially in the process of independent learning of the English language. It also analyzes the use of advanced AI platforms such as ChatGPT, Duolingo, Grammarly and Replika in education.